Maximizing toxicity of pyrethroid insecticides Sumicidin by using anis seed extracts Pimpenella anisium as a synergist against adult of confused flour beetles Tribolium confusum. - wahied, Rashaa (University of Thi-Qar Journal of Science, 2011)
This study deals with using of anis seeds extracts to synergy the synthetic pyrethroid insecticide Sumicidin against confused flour beetles Tribolium confusum .Also found percentsof mortality to different concentrations of insecticides alone and mixture with extract bydifferent mixture ratios. Lethal concentration of 50(Lc50) value was concluded thensynergistic ratio for sumicidin alone tests and the using ratio tests mixture too. Results showthat mortality ratio of insects exposed to sumicidin alone were increased more than to mixture,so the mortality ratio of the concentration (0.1)ml/l as (24.09) in the mixture ratio (1:1) and(44.4)in (1:3)for the same concentration while there was no mortality ratio in sumicidin alonetest .Experimented insects were recorded the highest responsible degree to sumicidin alone in(0.5)ml/l concentration while ahigh degree for the mixture of sumicidin and extracte was in(1:3) as (44.4) in (0.1)ml/l concentration .Also study was showed the Lc50value for sumicidinalone (5.4)and for mixtures ratios (2.5) (0.5) respectively .Study showed that the anis extractwas synergetic sumicidin as(2.3)fold in the first mixture ratio and (1.8)fold in the secondmixture ratio.